A Survey of Methods Used to Control Piezoelectric Tube Scanners in High‐Speed AFM Imaging. Issue 4 (17th January 2018) - Rana, Md. Sohel; Pota, Hemanshu R.; Petersen, Ian R.
Abstract: In most nanotechnology applications, speed and precision are important requirements for obtaining good topographical maps of material surfaces using atomic force microscopes (AFMs), many of which use piezoelectric tube scanners (PTSs) for scanning and positioning at nanometric resolutions. For control engineers, the PTS is particularly interesting since its ability to enable the AFM to undertake 3D imaging is entirely dependent upon the use of a feedback loop. However, it suffers from various intrinsic problems that degrade its positioning performance, such as: (i) lightly damped low‐frequency resonant modes due to its mechanical structure; (ii) nonlinear behavior due to hysteresis and creep; (iii) the cross‐coupling effect between its axes (in 3D positioning systems such as AFMs); and (iv) effect of thermal drift. This article presents a survey of the literature on the PTS, an overview of a few existing innovative solutions for its nanopositioning and future research directions. This article will help the reader to walk around the present development of the PTS aimed at meeting the requirements for high‐speed AFM imaging.